PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001 PADA KONTRAKTOR PT. X - Arief Darmawan; Sidiq Wacono; Jonathan Saputra (Construction and Material Journal, 2020)
Infrastructures development in Indonesia is experiencing a high increase. However, many construction failures were due to construction that was not following the predetermined quality. Data obtained from the Investigation of the PNK Technical Team in 2013 contained 5 cases of construction project failure handled by the authorities with a total loss of more than 5 billion to the state. The reality shows that many construction service businesses have names but do not have the supporting facilities. Therefore, data collection aims to analyze the application of the ISO 9001: 2015 application quality management system and its application constraints. Processing data use descriptive statistical analysis and using SPSS version 25 software. The data testing techniques used include validity, reliability, and descriptive hypothesis. The data was collected using a questionnaire method for construction employees in the Design Project for the Tanjung Barat Station Flats. This analysis indicates that the application of the ISO 9001: 2015 quality management system by taking into account all the points from clause 4 to clause 10 is 85.19% and is in the excellent category (80-100%). Factors that become obstacles in implementing ISO 9001: 2015 are due to the lack of socialization regarding the application of ISO 9001, documented information, and communication between project teams. Keywords : ISO 9001, ISO 9001:2015, Quality Management System.